1997
DOI: 10.1002/(sici)1097-0142(19970115)79:2<380::aid-cncr22>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of cyclin D1 in squamous cell carcinoma of the head and neck and the prognostic value of chromosomal abnormalities and cyclin D1 overexpression

Abstract: Overexpression of cyclin D1 and 11q13 rearrangements are independent prognostic factors for SCCHN. In general, DNA amplification results in overexpression of cyclin D1, but additional genetic mechanisms are involved in the deregulation. Furthermore, oncogenes at 11q13 besides CCND1 may be involved in the tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(82 citation statements)
references
References 26 publications
5
73
0
4
Order By: Relevance
“…Loss of CCND1 was significantly associated with nontumor lesions in this study cohort, suggesting genomic instability/chromosomal aneuploidy events in the direction of corresponding gain of CCND1 in tumor lesions ( P < 0.001, univariate analysis). Overexpression and/or amplification of CCND1 is reported in 35%–65% of patients with HNSCC and is associated with poor prognosis [5658]. Its expression is deregulated in preinvasive lesions adjacent to invasive tumors and is associated with increased chromosomal instability and the likelihood of subsequent gene amplification.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of CCND1 was significantly associated with nontumor lesions in this study cohort, suggesting genomic instability/chromosomal aneuploidy events in the direction of corresponding gain of CCND1 in tumor lesions ( P < 0.001, univariate analysis). Overexpression and/or amplification of CCND1 is reported in 35%–65% of patients with HNSCC and is associated with poor prognosis [5658]. Its expression is deregulated in preinvasive lesions adjacent to invasive tumors and is associated with increased chromosomal instability and the likelihood of subsequent gene amplification.…”
Section: Resultsmentioning
confidence: 99%
“…There may be two reasons for this difference: First, compared to other subsites in the oral cavity, tongue SCC is characterized by a more aggressive biological phenotype, with a high-degree of cervical lymph node spread that might be reflected at molecular level, such as with cyclin D1 expression. Second, cyclin D1 may be differentially expressed in various anatomical sites in the oral cavity [18], [41], [42]. Regarding ethnicity, two studies previously reported the clinicopathological significance of cyclin D1 overexpression in Caucasian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although this method is a semiquantitative technique, IHC analysis is the most commonly used, simplest, and cheapest protocol in clinical work [30]. Moreover, it is believed that cyclin D1 protein overexpression may occur via other mechanisms besides gene amplification, and the measurement of protein levels would be more informative than cyclin D1 DNA copies [19], [31], [32], [33]. According to the obtained results, low cyclin D1 expression at pretreatment forecasts a better clinical response and an improved DFS and OS in neoadjuvant chemotherapy patients.…”
Section: Discussionmentioning
confidence: 99%